In vivo Confocal Microscopic Evaluation of Previously Neglected Oval Cells in Corneal Nerve Vortex: An Inflammatory Indicator of Dry Eye Disease - Jing, Dalan; Jiang, Xiaodan; Chou, Yilin; Wei, Shanshan; Hao, Ran; Su, Jie; Li, Xuemin (Frontiers in Medicine, 2022)
This study aimed to investigate the association of between previously neglected oval cells located in the corneal vortex and dry eye disease (DED). This was an observational, prospective study involving 168 patients with different degrees of DED. In vivo confocal microscopy was used to observe the corneal sub-basal nerves and Langerhans cells (LCs) in the corneal vortex and periphery. Bright and oval cells were also observed in the corneal vortex. An artificial intelligence technique was used to generate sub-basal nerve fibre parameters. The patients were divided into three groups based on presence of inflammatory cells. Group 2 patients showed a significant increase in the corneal peripheral nerve maximum length and average corneal peripheral nerve density. Patients in Group 3 had more LCs than others. A bright and oval cell was identified in the corneal vortex, which might be a type of immature LC related to the disease severity of DED.